2004
DOI: 10.1073/pnas.0308382101
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral analgesic blockade of hypernociception: Activation of arginine/NO/cGMP/protein kinase G/ATP-sensitive K + channel pathway

Abstract: The final step in the direct restoration of the nociceptor threshold by peripheral administration of morphine and dipyrone was recently suggested to result from the opening of ATP-sensitive K ؉ channels (K ATP ؉ ). This channel is known to be open either directly by cGMP or indirectly via protein kinase G (PKG) stimulation. In the present study, it was shown that the blockade was caused by a specific PKG inhibitor (KT5823) of the antinociceptive effect of morphine and dipyrone on acute hypernociception and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 63 publications
6
120
0
8
Order By: Relevance
“…In the case of the latter, this pathway might cause a hyperpolarization of nociceptive neurons, counteracting their enhanced excitability during the inflammatory process. In the schematic representation of the present hypothesis, we also indicate the possible mechanism of NO modulating K ATP currents indirectly through the activation of cGMP/PKG signaling (33). The development of drugs that mimic the action of morphine on this pathway may represent strategies for the treatment of inflammatory pain.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the latter, this pathway might cause a hyperpolarization of nociceptive neurons, counteracting their enhanced excitability during the inflammatory process. In the schematic representation of the present hypothesis, we also indicate the possible mechanism of NO modulating K ATP currents indirectly through the activation of cGMP/PKG signaling (33). The development of drugs that mimic the action of morphine on this pathway may represent strategies for the treatment of inflammatory pain.…”
Section: Resultsmentioning
confidence: 99%
“…These contradictions might be explained by considering that NO is a controversial molecule with dual effects, depending on its concentrations, NOS isoforms, redox balance, and the function of neuron subpopulations (Kawabata, 1994;Zhang et al, 2006). On one hand, increased NO production has been shown to produce antinociception (Bulutcu et al, 2002;Galdino et al, 2010;Garrido-Suárez et al, 2009;Granados-Soto et al, 1997;Sachs et al, 2004), on the other hand, NOS inhibitors elicit antinociception in some models of acute and persistent pain (De Alba et al, 2006;Milovanović et al, 2009;Yonehara et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other potassium channels blockers such as tetraethylammonium or 4-aminopyridine had no effect on the antinociception. Several of these reports indicate a linkage between the cyclic GMP signalling pathway and activation of K ATP (Lazaro-Ibanez et al 2001;Soares and Duarte 2001;Sachs et al, 2004). Indeed, studies of other cellular systems have demonstrated that cyclic GMP can lead to the activation of K ATP (Kubo et al 1994;Murphy and Brayden, 1995;Armstead 1997Armstead , 1998Schwingshackl et al 2002).…”
Section: Introductionmentioning
confidence: 99%